Long-Term Stability of Neuroaxonal Structure in Alemtuzumab-Treated Relapsing–Remitting Multiple Sclerosis Patients. Issue 1 (March 2020) - Chan, Jillian K.; Hernandez Martínez de Lapiscina, Elena; Taylor, Carolyn; Nguyen, Ai-Lan; Alba-Arbalat, Salut; Devonshire, Virginia; Sayao, Ana-Luiza; Carruthers, Robert; Costello, Fiona; Traboulsee, Anthony
Abstract : Background: Patients with multiple sclerosis (MS) experience progressive thinning in optical coherence tomography (OCT) measures of neuroaxonal structure regardless of optic neuritis history. Few prospective studies have investigated the effects of disease-modifying therapies on neuroaxonal degeneration in the retina. Alemtuzumab is a monoclonal antibody shown to be superior to interferon β-1a in treating relapsing–remitting MS (RRMS). The purpose of this study was to assess the effects of alemtuzumab and first-line injectable treatments on OCT measures of neuroaxonal structure including peripapillary retinal nerve fiber layer (RNFL) thickness and combined ganglion cell–inner plexiform (GCIP) layer volume in RRMS patients followed up over 5 years. Methods: In this retrospective pilot study with prospectively collected double cohort data, spectral domain OCT measures of RNFL thickness and GCIP volume were compared between alemtuzumab-treated RRMS patients (N = 24) and RRMS patients treated with either interferon-β or glatiramer acetate (N = 21). Results: Over a median of 60 months (range 42–60 months), the alemtuzumab cohort demonstrated a change in the mean RNFL thickness (thinning from baseline) of −0.88 μm (95% confidence interval [CI] −2.63 to 0.86; P = 0.32) and mean GCIP volume of +0.013 mm 3 (95% CI −0.006 to 0.032; P = 0.18). Over the same time period, the first-line therapy–treated cohort demonstrated greater degrees of RNFL thinning (mean change in RNFL thickness was −3.65 μm [95% CI −5.40 to −1.89; P = 0.0001]). There was also more prominent GCIP volume loss relative to baseline in the first-line therapy group (−0.052 mm 3 [95% CI −0.070 to −0.034; P < 0.0001]). Conclusions: Alemtuzumab-treated patients with RRMS demonstrated relative stability of OCT-measured neuroaxonal structure compared with RRMS patients treated with either interferon-β or glatiramer acetate over a 5-year period. These findings, along with previous demonstration of improved brain atrophy rates, suggest that alemtuzumab may offer long-term preservation of neuroaxonal structure in patients with RRMS.